Zika Virus Infection Control: A Perspective Towards Natural Medicine (REVISTA SAYWA, 2021)
Zika virus infection is a worldwide problem, it can have severe complications such as death. However, there is no specific treatment. This article aims to review the plant extracts that have been shown to inhibit the proliferation of this virus, in vitro, as a possible therapeutic strategy.